Analysis of Current Status and Prospects of Parachute-Based Airborne Wind Energy Technology - LUO Bixiong, REN Zongdong, LIU Haiyang, LI Xiaoyu (Dianli jianshe, 2025)
[Objective] Airborne wind energy（AWE）technology utilizes faster and more stable wind speeds at higher altitudes and offers higher energy density and power generation efficiency than traditional wind power generation. This study explored the current status and prospects of AWE technology，with a particular focus on parachute-based ground-generated high-altitude wind power technology. [Methods] This article outlines the technological routes of AWE systems（AWESs）using two main approaches（ground-gen and air-gen）and discusses their respective technical challenges and the current status of development. Special attention is paid to the parachute-based ground-gen AWES，with a detailed introduction to its working principle，system composition，and engineering case analysis. Parachute-based technology effectively captures and converts wind energy through the coordinated operation of aerial，traction，and ground components. By analyzing the specific implementation of the Jixi high-altitude wind power project in China，this article demonstrates the practical application and effectiveness of parachute-based ground-gen AWE technology. [Results] The project successfully achieved high-altitude wind power generation，which could output kilowatt-level power at low altitudes and megawatt levels over 5 km，thus verifying the feasibility and advantages of the technology. [Conclusions] The Jixi Project proved the feasibility of this technology，which features scalability，high safety，and high resource utilization efficiency. It also achieves a high wind energy conversion efficiency and can capture wind resources at altitudes over 1 km by increasing the length of the tether and adjusting the launch angle. In the “Three North” regions with abundant wind resources，this technology can achieve MW-level power generation at an altitude of 1000 m and further upgrade the power generation capacity by increasing the number of doing-work parachutes，holding significant implications for renewable energy development.